Development of Interactive Educational Pop-Up Book Media "Pelangi di Rumah Kita" on Positive Parenting for Early Childhood Parents in Kindergarten - Asra Dewi; Abdul Saman; Usman Bafadal; Abdul Hakim; Herlina (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Many parents of young children continue to struggle to apply positive parenting practices consistently, largely due to limited access to practical, engaging educational resources. Addressing this gap, the present study aimed to develop and evaluate an Interactive Educational Pop-Up Book entitled “Pelangi di Rumah Kita” designed to enhance parents’ understanding of positive parenting in kindergarten settings. This study employed a Research and Development (R&D) approach using the 4-D model (define, design, develop, and disseminate). The product was validated by two experts and field-tested with 30 parents from three kindergartens in Sidrap Regency. Data were collected through observations, interviews, expert validation sheets, parent response questionnaires, and pretest–posttest instruments. The validation process yielded an average total validity score of 3.22, indicating that the product met the validity criteria. The practicality assessment showed a very high level of usability (99.83%), reflecting positive parental responses regarding ease of use, attractiveness, and relevance. Effectiveness testing using the Wilcoxon Signed-Rank Test demonstrated a significant increase in parents’ scores from 60 (75%) on the pretest to 79.8 (99.75%) on the posttest (Asymp. Sig. = 0.000 < 0.05). These findings indicate that the developed media is valid, practical, and effective in strengthening parents’ understanding and application of positive parenting practices. Keywords: early childhood education, early childhood parents, interactive educational pop-up book, media development, positive parenting